EDUKASI KESEHATAN DAN PENDIDIKAN ANAK USIA SEKOLAH PASCA PANDEMI COVID 19 - S, Amrita; Nafilah El Hafizah; Wisnu Aditya (Politeknik Negeri Sriwijaya, 2023)
Tahunan Village is one of the villages in Sale Sub-district, Rembang Regency. This village has a lot of potential, namely there are various home industries, but they have not been well developed. The existence of this home industry opportunity is also getting less attention because during the Covid-19 pandemic many community activities were stopped, causing new problems in the fields of health and education. After entering the new normal after the Covid-19 pandemic, observations were made in Tahunan Village with the aim of reviewing community understanding in the fields of health and education through community assistance activities. The implementation of this assistance is in the form of education to the community in the fields of health and education. In the field of education, the people who were given education were school-age children at the elementary school level. The results obtained are the lack of understanding of the community regarding a healthy environment and the use of computer and internet technology in the health sector. Keywords: health, education, pandemic, community assistance